E. Œ. Somerville and Martin Ross : female authorship and literary collaboration - Jamison, Anne (Book collections on Project MUSE., 2016)
This book explores the remarkable collaboration of one of the most prominent and successful female literary partnerships at work in the late nineteenth century; Irish authors, Edith Somerville (1858-1949) and Violet Martin/Martin Ross (1862-1915). Based on extensive and original archival research, it reorients traditional thinking about Somerville and Ross's partnership and rethinks the collaboration beyond a purely domestic and personal affair. The collaboration is here viewed as a significant part of the two women's lifelong but always complex feminist ethic, as well as a defiant and oft-times subversive cultural position within Irish and Victorian literary society more generally. Taking its cue from the legal aesthetics of nineteenth-century definitions of authorship and copyright, this book significantly expands the existing parameters of debate surrounding these authors and argues for their dual artistic practice to be understood as a type of authorial dissidence. Sidestepping Somerville and Ross's major texts, the book sheds new light on the two women's lesser studied--but equally important--travel writing, essays, short fiction, life writing, and extensive personal archival material, opening up new avenues of enquiry into the complexities of gender, class, and nationality in nineteenth-century Ireland. The book thus significantly interrogates the idea of collaboration both from the point of view of the authors, their publishers and readers, as well as their texts, and both deepens, as well as challenges, current literary history's broader understanding and treatment of nineteenth-century female authorship and literary production in particularly resonant ways.